The Effects of Vocabulary and Grammar Mastery Toward Student’s Reading Comprehension of Grade X of State Senior High School Students in West Jakarta - Ulfatussyarifah Ulfatussyarifah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The objective of the research is to get empirical data concerning the effects of vocabulary and grammar mastery towards student’s reading comprehension. This research is done by Kolgomorov-Smirnov method, ANOVA Table, Proportional Correct for testing the item difficulties, Biserial Coefficient and Kuder Richarson testing. Samples are taken of the achievable population were 60 students from grade eleven of social and science in section 3 and 4 at SMA Negeri 14 Jakarta. Data collection is conducted by giving test for reading comprehesion, test for vocabulary mastery, and test for grammar. The results show that there are significant effects of vocabulary mastery and grammar mastery altogether towards student’s reading comprehension of X1 grade at state Senior High Schools in West Jakarta. It is proven by the score of Fo = 4,160 dan Sig. = 0,021 < 0, 05. There is a significant effect of vocabulary mastery towards student’s reading comprehension as it is proved by the score of to = 2,662 dan Sig. = 0,001 < 0,05. There is a significant effect of grammar mastery towards student’s reading comprehension as it is proved by the score of to =-0,222 dan Sig. = 0,082 > 0,05 Key words: vocabulary mastery, grammar mastery, reading comprehension